Associations between left bundle branch block with different PR intervals, QRS durations, heart rates and the risk of heart failure: a register-based cohort study using ECG data from the primary care setting. Issue 1 (11th February 2021) - Søndergaard, Marc Meller; Riis, Johannes; Bodker, Karoline Willum; Hansen, Steen Møller; Nielsen, Jesper; Graff, Claus; Pietersen, Adrian Holger; Nielsen, Jonas Bille; Tayal, Bhupendar; Polcwiartek, Christoffer; Torp-Pedersen, Christian; Soegaard, Peter; et al.
Abstract : Aim: Left bundle branch block (LBBB) is associated with an increased risk of heart failure (HF). We assessed the impact of common ECG parameters on this association using large-scale data. Methods and results: Using ECGs recorded in a large primary care population from 2001 to 2011, we identified HF-naive patients with a first-time LBBB ECG. We obtained information on sex, age, emigration, medication, diseases and death from Danish registries. We investigated the association between the PR interval, QRS duration, and heart rate and the risk of HF over a 2-year follow-up period using Cox regression analysis. Of 2471 included patients with LBBB, 464 (18.8%) developed HF during follow-up. A significant interaction was found between QRS duration and heart rate (p<0.01), and the analyses were stratified on these parameters. Using a QRS duration <150 ms and a heart rate <70 beats per minute (bpm) as the reference, all groups were statistically significantly associated with the development of HF. Patients with a QRS duration ≥150 ms and heart rate ≥70 bpm had the highest risk of developing HF (HR 3.17 (95% CI 2.41 to 4.18, p < 0.001). There was no association between the PR interval and HF after adjustment. Conclusion: Prolonged QRS duration and higher heart rate were associated with increased risk of HF among primary care patients with LBBB, while no association was observed with PR interval. Patients with LBBB with both a prolonged QRS duration (≥150 ms) and higher heart rate (≥70 bpm) have the highest risk of developing HF.